Analisis Efektivitas Promosi Perguruan Tinggi Dengan Penerapan Model AISAS - Danang Satrio; Rika Adriyana (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2023)
ABSTRACT Technological advances today, especially the internet of things, are widely used by people in their daily transactions, communication and searching for various information. One of the promotional media used in universities is in the form of visual communication media using the AISAS model in describing online promotions used by universities. This study aims to analyze the effectiveness of promotions carried out by the promotion of new student admissions (PMB) of Pekalongan University based on the concept of marketing communication and technological developments, namely attention, interest, search, action, and share (AISAS model). This study used a descriptive approach by distributing questionnaires to prospective new student recipients. With this research, it can be useful to evaluate the new student admissions section so that in making promotions, it is necessary to pay attention to the AISAS aspect so that the number of student applicants is much higher. The results of this study show that online promotion has a significant effect on attention, interest, and share. While promotion does not have a significant effect on search and action. Attention has a significant positive impact on interest. Interest has a significant positive effect on search. Search has a positive and significant effect on actions while actions do not have a significant effect on shares. Keywords: Marketing Communications, Promotion, College, AISAS